Variations in head impact rates in male and female high school soccer - Huber, C. M.; Patton, D. A.; Jain, D.; Master, C. L.; Margulies, S. S.; McDonald, C. C.; Arbogast, K. B. (Medicine & Science in Sports & Exercise, 2021)
Introduction: Repetitive head impacts in soccer have been linked to short-term neurophysiological deficits, and female soccer players have higher concussion rates than males. These findings have inspired investigation into gender differences in head impact exposure and how head impact rate contributes to the cumulative effect of head impact exposure on neurological outcomes. Various periods of exposure have been used to calculate head impact rates, including head impacts per season, game, and player-hour. Purpose: The aim of this study was to apply different methodological approaches to quantify and compare head impact rates by gender for two seasons of high school varsity soccer. Methods: Video review was used to confirm all events recorded by a headband-mounted impact sensor and calculate playing time for all players. Impact rates were calculated per athlete exposure (presence and participation) and per player-hour (scheduled game time, individual play time, and absolute time). Results: Impact rates per athlete exposure ranged from 2.5 to 3.2 for males and from 1.4 to 1.6 for females, and impact rates per player-hour ranged from 2.7 to 3.8 for males and from 1.0 to 1.6 for females. The exposure calculation method significantly affected head impact rates; however, regardless of approach, the head impact rate for males was higher, up to threefold, than for females. Individual head impact exposure varied substantially within a team with one in five players experiencing no impacts. Conclusions: Overall, the gender differences found in this study indicate that males experience higher head impact exposure compared with females. Future studies are needed to understand potential clinical implications of variability in head impact exposure and reconcile higher female concussion rates with the reduced head impact rates presented herein.